Thermoplastic compositions, methods of making same, and articles made therefrom
Through a combination of poly(phenylene ether), poly(phenylene ether)-poly(siloxane) block copolymer in a specific proportion, a reinforcement filler and an organophosphate flame retardant, a thermoplastic composition with low flammability, high mechanical strength and high impact strength was prepared, which solved the problem of insufficient flammability and strength of poly(arylene ether) materials in thin-wall applications, and achieved excellent performance combinations.
Patent Information
- Application Number
- CN202380089534.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-12-13
- Publication Date
- 2025-08-05
AI Technical Summary
Existing poly(arylether) materials have problems with high flammability, insufficient mechanical strength and impact resistance in thin-wall applications.
The thermoplastic composition is prepared by melt mixing and optimizing its performance using a composition of a first poly(phenylene ether), a poly(phenylene ether)-poly(siloxane) block copolymer in a specific proportion, a reinforcing filler, an organophosphate flame retardant and an impact modifier.
It achieves a combination of low flammability, high mechanical strength, high heat resistance and high impact strength, meets the UL-94 flammability level V0 standard, and has good hydrolysis stability.
Smart Images

Figure BDA0005470972240000021 
Figure BDA0005470972240000031 
Figure BDA0005470972240000041
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of European patent application 22216851.0 filed on December 28, 2022, the contents of which are incorporated herein by reference in their entirety.
[0003] background
[0004] Poly(arylene ethers) are commercially attractive materials because they possess a unique combination of properties such as high temperature resistance, dimensional and hydrolytic stability, and electrical properties.
[0005] There is a continuing need in the art for a poly(arylene ether) composition with low flammability, particularly for thin wall applications. It would be advantageous if the composition, in addition to low flammability, also exhibited high mechanical strength, high heat resistance, and high impact strength.
[0006] Overview
[0007] A thermoplastic composition comprises 20 to 40 weight percent of a first poly(phenylene ether); 20 to 40 weight percent of a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a block copolymer of a poly(phenylene ether)-poly(siloxane) and a second poly(phenylene ether); 8 to 35 weight percent of a reinforcing filler; 10 to 20 weight percent of an organophosphate flame retardant; and optionally 1 to 15 weight percent of an impact modifier comprising a hydrogenated block copolymer of an alkenyl aromatic and a conjugated diene; wherein the weight percent of each component is based on the total weight of the composition.
[0008] Another aspect is a thermoplastic composition comprising: a first poly(phenylene ether); a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); a reinforcing filler; an organophosphate flame retardant; and an optional impact modifier comprising a hydrogenated block copolymer of an alkenyl arene and a conjugated diene; wherein the thermoplastic composition comprises less than 1 weight percent of a hydrocarbon resin. the thermoplastic composition; and wherein a molded sample of the composition exhibits: a UL-94 flammability rating of V0 as measured using a 1.0 mm test bar after conditioning at 23° C. for 48 hours and at 70° C. for 168 hours; a UL-94 flammability rating of V0 as measured using a 0.75 mm test bar after conditioning at 23° C. for 48 hours and at 70° C. for 168 hours; a UL-94 flammability rating of V0 as measured using a 0.5 mm test bar after conditioning at 23° C. for 48 hours and at 70° C. for 168 hours; and a UL-94 flammability rating of V0 as measured using a 0.3 mm test bar after conditioning at 23° C. for 48 hours and at 70° C. for 168 hours; and a tensile modulus of 3500 MPa or greater as measured in accordance with ASTM D638.
[0009] The method of preparing the composition comprises melt-mixing the components of the composition.
[0010] Articles comprising the composition represent another aspect of the present disclosure.
[0011] The above described and other features are exemplified by the following detailed description.
[0012] Detailed description
[0013] The present inventors have unexpectedly discovered that a specific thermoplastic composition can provide a desirable combination of properties. More specifically, a composition comprising specific amounts of a first poly(phenylene ether), a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer, and a second poly(phenylene ether), a reinforcing filler, an organophosphate flame retardant, and optionally an impact modifier comprising a hydrogenated block copolymer of an alkenyl arene and a conjugated diene can provide a desirable combination of low flammability, high mechanical strength, high heat resistance, high impact strength, and hydrolysis resistance.
[0014] Thus, one aspect of the present invention is a thermoplastic composition. The thermoplastic composition comprises a first poly(phenylene ether). Herein, the poly(phenylene ether) comprises repeating structural units of formula (1)
[0015]
[0016] Among them, Z 1 Each occurrence is independently halogen, unsubstituted or substituted C 1-12 Hydrocarbon group, provided that the hydrocarbon group is not a tertiary hydrocarbon group, C 1-12 Hydrocarbon sulfide, C 1-12 Hydroxyl or C 2-12 a haloalkyloxy group (wherein at least two carbon atoms separate the halogen atom from the oxygen atom); Z 2 Each occurrence is independently hydrogen, halogen, unsubstituted or substituted C 1-12 -hydrocarbon group, provided that the hydrocarbon group is not a tertiary hydrocarbon group, C 1-12 Hydrocarbon sulfide, C 1-12 Hydroxyl or C 2-12 Halogenated hydrocarbyl (wherein there are at least two carbon atoms separating the halogen atom from the oxygen atom). As used herein, the term "hydrocarbyl", whether used alone or as a prefix, suffix, or fragment of another term, refers to a residue containing only carbon and hydrogen. The residue may be aliphatic or aromatic, linear, cyclic, bicyclic, branched, saturated, or unsaturated. It may also contain a combination of aliphatic, aromatic, linear, cyclic, bicyclic, branched, saturated, and unsaturated hydrocarbyl moieties. However, when a hydrocarbyl residue is described as substituted, it may optionally contain heteroatoms in addition to the carbon and hydrogen members of the substituent residue. Thus, when specifically described as substituted, the hydrocarbyl residue may also contain one or more carbonyl groups, amino groups, hydroxyl groups, etc., or it may contain heteroatoms within the backbone of the hydrocarbyl residue. For example, Z 1 It may be a di-n-butylaminomethyl group formed by the reaction of a terminal 3,5-dimethyl-1,4-phenyl group with the di-n-butylamine component of an oxidative polymerization catalyst.
[0017] In one aspect, the first poly(phenylene ether) comprises 2,6-dimethyl-1,4-phenylene ether repeating units, ie, repeating units according to formula (2)
[0018]
[0019] 2,3,6-trimethyl-1,4-phenylene oxide repeating units, or a combination thereof.
[0020] The first poly(phenylene ether) may comprise molecules having aminoalkyl-containing end groups, typically located in an ortho position relative to the hydroxyl group. Tetramethyldiphenoquinone (TMDQ) end groups are also often present, typically obtained from a reaction mixture containing 2,6-dimethylphenol, which produces tetramethyldiphenoquinone as a byproduct. The poly(phenylene ether) may be a homopolymer, copolymer, graft copolymer, ionomer, or block copolymer, as well as combinations thereof.
[0021] In one aspect, the first poly(phenylene ether) can have an intrinsic viscosity of 0.03 to 2 deciliters per gram (dl / g). For example, the intrinsic viscosity of the poly(phenylene ether) as measured in chloroform at 25° C. using an Ubbelohde viscometer can be greater than 0.25 dl / g, or 0.25 to 1.7 dl / g, specifically 0.25 to 0.6 dl / g, more specifically 0.25 to 0.4 dl / g, even more specifically 0.35 to 0.50 dl / g, or 0.4 to 0.6 dl / g.
[0022] The first poly(phenylene ether) can be prepared by an oxidative polymerization method. In this method, the first poly(phenylene ether) is the product of oxidative polymerization of a monomer mixture containing a monohydroxyphenol, which can be as described above.
[0023] The first poly(phenylene ether) may be present in an amount of 20 to 40 weight percent, based on the total weight of the thermoplastic composition. Within this range, the first poly(phenylene ether) may be present in an amount of 20 to 38 weight percent, or 21 to 39 weight percent, or 22 to 36 weight percent, or 22 to 35 weight percent, each based on the total weight of the composition.
[0024] In addition to the first poly(phenylene ether), the thermoplastic composition further comprises a poly(phenylene ether)-poly(siloxane) block copolymer. As used herein, the term "poly(phenylene ether)-poly(siloxane) block copolymer" refers to a block copolymer comprising at least one poly(phenylene ether) block and at least one polysiloxane block. The poly(phenylene ether)-polysiloxane block copolymer can be prepared by an oxidative copolymerization process. In this process, the poly(phenylene ether)-polysiloxane block copolymer is obtained by oxidative copolymerization of a monomer mixture comprising a monophenol and a hydroxyaryl-terminated polysiloxane. In one aspect, the monomer mixture comprises 70 to 99 parts by weight of a monophenol and 1 to 30 parts by weight of a hydroxyaryl-terminated polysiloxane, based on the total weight of the monophenol and the hydroxyaryl-terminated polysiloxane. The hydroxyaryl-di-terminated polysiloxane may comprise a plurality of repeating units having the structure
[0025]
[0026] where R 8 Each occurrence is independently hydrogen, C 1-12 Hydrocarbon or C 1-12 Halogenated hydrocarbon group; and the two terminal units have the following structure
[0027]
[0028] Where Y is hydrogen, C 1-12 Hydrocarbon, C 1-12 alkoxy, or halogen, and wherein R 9Each occurrence is independently hydrogen, C 1-12 Hydrocarbon or C 1-12 In one aspect, R 8 and R 9 Each occurrence of is methyl and Y is methoxy.
[0029] In one aspect, the monohydric phenol comprises 2,6-dimethylphenol and the hydroxyaryl-terminated polysiloxane has the structure
[0030]
[0031] Here, n is on average 5 to 100, especially 30 to 60.
[0032] The oxidative copolymerization method produces a poly(phenylene ether)-polysiloxane block copolymer as the desired product, and a poly(phenylene ether) (without polysiloxane blocks) as a byproduct. There is no need to separate the poly(phenylene ether) from the poly(phenylene ether)-polysiloxane block copolymer. The poly(phenylene ether)-polysiloxane block copolymer can therefore be used as a "reaction product" comprising poly(phenylene ether) and a poly(phenylene ether)-polysiloxane block copolymer. Some separation procedures (e.g., isopropanol precipitation) can ensure that the reaction product is substantially free of residual hydroxyaryl-terminated polysiloxane starting material. In other words, these separation procedures ensure that the polysiloxane in the reaction product is essentially all poly(phenylene ether)-polysiloxane block copolymer. Detailed methods for forming poly(phenylene ether)-polysiloxane block copolymers are described in U.S. Patents 8,017,697 and 8,669,332 to Carrillo et al.
[0033] In one aspect, the poly(phenylene ether)-polysiloxane block copolymer can, for example, contribute 0.05 to 2 weight percent, specifically 0.1 to 1 weight percent, and more specifically 0.2 to 0.8 weight percent, of siloxane groups to the total composition.
[0034] The composition comprises 20 to 40 weight percent of a poly(phenylene ether)-poly(siloxane) block copolymer reaction product, based on the total weight of the composition. Within this range, the first poly(phenylene ether) can be present in an amount of 20 to 38 weight percent, or 21 to 39 weight percent, or 22 to 36 weight percent, or 22 to 35 weight percent, based on the total weight of the composition.
[0035] In one aspect, the first poly(phenylene ether) and the poly(phenylene ether)-poly(siloxane) block copolymer reaction product can be present in a weight ratio of 1.75:1 to 1:1.75, or 1.5:1 to 1:1.5, or 1.25:1 to 1:1.25, or 1.1:1 to 1:1.1, or 1.05:1 to 1:1.05.
[0036] In addition to the first poly(phenylene ether) and the poly(phenylene ether)-poly(siloxane) block copolymer, the thermoplastic composition further comprises a reinforcing filler.
[0037] Possible fillers or reinforcing agents include, for example, mica, clay, feldspar, quartz, quartzite, perlite, tripoli, diatomaceous earth DE, aluminum silicate (mullite), synthetic calcium silicate, fused silica, fumed silica, sand, boron-nitride powder, boron-silicate powder, calcium sulfate, calcium carbonate (e.g., chalk, limestone, marble, and synthetic precipitated calcium carbonate), talc (including fibrous, modular, acicular, and lamellar talc), wollastonite, hollow or solid glass spheres, silicate spheres (e.g., silicate spheres), and silicate spheres. spheres, cenospheres, aluminosilicates or armospheres, kaolin, whiskers (silicon carbide, alumina, boron carbide, iron, nickel, or copper), continuous and chopped carbon or glass fibers, molybdenum sulfide, zinc sulfide, barium titanate, barium ferrite, barium sulfate, heavy spar, TiO2, alumina, magnesium oxide, granular or fibrous aluminum, bronze, zinc, copper, or nickel, glass flakes, flaked silicon carbide, flaked aluminum diboride, flaked aluminum, steel flakes, natural fillers (e.g., wood flour, fibrous cellulose, cellulose), cotton, sisal, jute, starch, lignin, ground nutshells, or rice grain husks), reinforcing organic fiber fillers such as poly(ether ketones), polyimides, polybenzoxazoles, poly(phenylene sulfide), polyesters, polyethylene, aromatic polyamides, aromatic polyimides, polyetherimides, polytetrafluoroethylene, and poly(vinyl alcohol)), and combinations thereof.Fillers and reinforcing agents that are minimized or excluded from the composition may be coated with a layer of metallic material to promote conductivity or surface treated with silanes to improve adhesion and dispersion in the polymer matrix.
[0038] In one aspect, the reinforcing filler can be reinforcing fiber. Exemplary reinforcing fiber can include glass fiber, carbon fiber, mineral fiber or a combination thereof. In a specific aspect, the reinforcing filler can include glass fiber.
[0039] The reinforcing filler can comprise 8 to 35 weight percent, based on the total weight of the thermoplastic composition. Within this range, the reinforcing filler can comprise 8 to 32 weight percent, or 10 to 30 weight percent, based on the total weight of the thermoplastic composition.
[0040] In addition to the first poly(phenylene ether), the poly(phenylene ether)-poly(siloxane) block copolymer, and the reinforcing filler, the thermoplastic composition further comprises an organophosphate flame retardant. Exemplary organophosphate compounds include: phosphates containing phenyl, substituted phenyl, or a combination of phenyl and substituted phenyl groups; resorcinol-based bisaryl phosphates, such as resorcinol bis(diphenyl phosphate); and those based on bisphenols, such as bisphenol A bis(diphenyl phosphate). In one aspect, the organophosphate is selected from tris(alkylphenyl)phosphate (e.g., CAS Reg. No. 89492-23-9 or CAS Reg. No. 78-33-1), resorcinol bis(diphenyl phosphate) (CAS Reg. No. 57583-54-7), bisphenol A bis(diphenyl phosphate) (CAS Reg. No. 181028-79-5), triphenyl phosphate (CAS Reg. No. 115-86-6), tris(isopropylphenyl)phosphate (e.g., CAS Reg. No. 68937-41-7), tert-butylphenyl diphenyl phosphate (CAS Reg. No. 56803-37-3), bis(tert-butylphenyl)phenyl phosphate (CAS Reg. No. 65652-41-7), tris(tert-butylphenyl)phosphate (CAS Reg. No. 78-33-1), and combinations thereof.
[0041] In one aspect, the organophosphate comprises a bis-aryl phosphate according to formula (7)
[0042]
[0043] Where R is C independently each time it appears 1-12 Alkylene; R 16 and R 17 Each occurrence is independently C 1-5 Alkyl; R 12 、R 13 and R 15 Independently C 1-12 Hydrocarbon; R14 Each occurrence is independently C 1-12 alkyl; n is 1 to 25; and s1 and s2 are independently integers equal to 0, 1 or 2. In one aspect, OR 12 , OR 13 , OR 14 and OR 15 Independently derived from phenol, monoalkylphenol, dialkylphenol, or trialkylphenol.
[0044] Those skilled in the art will readily appreciate that bis-aryl phosphates are derived from bisphenols. Exemplary bisphenols include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-3,5-dimethylphenyl)methane, and 1,1-bis(4-hydroxyphenyl)ethane. In one aspect, the bisphenol includes bisphenol A.
[0045] In one aspect, the organophosphate comprises resorcinol bisdiphenyl phosphate, bisphenol A bisdiphenyl phosphate, or a combination thereof.
[0046] The organic phosphate ester can be present in the composition in an amount of 10 to 20 weight percent based on the total weight of the composition. Within this range, the organic phosphate ester can be present in an amount of 12 to 20 weight percent, or 14 to 18 weight percent.
[0047] The thermoplastic composition optionally further comprises an impact modifier comprising a hydrogenated block copolymer of an alkenyl aromatic hydrocarbon and a conjugated diene. For simplicity, this component is referred to as a "hydrogenated block copolymer". The hydrogenated block copolymer may comprise, based on its weight, 10 to 90 weight percent poly(alkenyl aromatic hydrocarbon) and 90 to 10 weight percent hydrogenated poly(conjugated diene). In one aspect, the hydrogenated block copolymer is a low poly(alkenyl aromatic hydrocarbon content) hydrogenated block copolymer, wherein the poly(alkenyl aromatic hydrocarbon) content is 10 to less than 40 weight percent, or 20 to 35 weight percent, or 25 to 35 weight percent, or 30 to 35 weight percent, all based on the weight of the low poly(alkenyl aromatic hydrocarbon content) hydrogenated block copolymer. In one aspect, the hydrogenated block copolymer is a high poly(alkenyl aromatic hydrocarbon content) hydrogenated block copolymer, wherein the poly(alkenyl aromatic hydrocarbon) content is 40 to 90 weight percent, or 50 to 80 weight percent, or 60 to 70 weight percent, all based on the weight of the high poly(alkenyl aromatic hydrocarbon content) hydrogenated block copolymer.
[0048] In one aspect, the hydrogenated block copolymer has a weight average molecular weight of 40,000 to 400,000 g / mol. The number average molecular weight and weight average molecular weight can be determined by gel permeation chromatography based on comparison with polystyrene standards. In one aspect, the hydrogenated block copolymer has a weight average molecular weight of 200,000 to 400,000 g / mol, or 220,000 to 350,000 g / mol. In one aspect, the hydrogenated block copolymer has a weight average molecular weight of 40,000 to 200,000 g / mol, or 40,000 to 180,000 g / mol, or 40,000 to 150,000 g / mol.
[0049] The alkenyl aromatic monomer used to prepare the hydrogenated block copolymer may have the structure of formula (6)
[0050]
[0051] Among them, R 5 and R 6 Each independently represents a hydrogen atom, C 1-8 Alkyl or C 2-8 Alkenyl; R 7 and R 11 Each independently represents a hydrogen atom, C 1-8 an alkyl group, a chlorine atom or a bromine atom; R 8 、R 9 and R 10 Each independently represents a hydrogen atom, C 1-8 Alkyl or C 2-8 Alkenyl, or R 8 and R 10 Together with the central aromatic ring, it forms a naphthyl group, or R 9 and R 10 Together with the central aromatic ring, a naphthyl group is formed. Specific alkenyl aromatic monomers include, for example, styrene, chlorostyrene (e.g., p-chlorostyrene), methylstyrene (e.g., α-methyl-styrene and p-methylstyrene), and tert-butylstyrene (e.g., 3-tert-butylstyrene and 4-tert-butylstyrene). In one aspect, the alkenyl aromatic monomer is styrene.
[0052] The conjugated diene used to prepare the hydrogenated block copolymer can be C 4-20 Conjugated dienes. Suitable conjugated dienes include, for example, 1,3-butadiene, 2-methyl-1,3-butadiene, 2-chloro-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, and the like, and combinations thereof. In one aspect, the conjugated diene is 1,3-butadiene, 2-methyl-1,3-butadiene, or a combination thereof. In one aspect, the conjugated diene is 1,3-butadiene.
[0053] The hydrogenated block copolymer is a copolymer comprising (A) at least one block derived from an alkenyl aromatic hydrocarbon and (B) at least one block derived from a conjugated diene, wherein the content of aliphatic unsaturated groups in block (B) is at least partially reduced by hydrogenation. In one aspect, the content of aliphatic unsaturated groups in block (B) is reduced by at least 50%, or at least 70%. The arrangement of blocks (A) and (B) includes a linear structure, a grafted structure, and a radial teleblock structure with or without branches. Linear block copolymers include tapered linear structures and non-tapered linear structures. In one aspect, the hydrogenated block copolymer has a tapered linear structure. In one aspect, the hydrogenated block copolymer has a non-tapered linear structure. In one aspect, the hydrogenated block copolymer comprises a (B) block comprising randomly incorporated alkenyl aromatic hydrocarbon monomers. Linear block copolymer structures include diblock (AB blocks), triblock (ABA blocks or BAB blocks), tetrablock (ABAB blocks), pentablock (ABABA blocks or BABAB blocks), and linear structures comprising a total of 6 or more (A) and (B) blocks. The molecular weight of each (A) block may be the same as or different from that of the other (A) blocks, and the molecular weight of each (B) block may be the same as or different from that of the other (B) blocks. In one aspect, the hydrogenated block copolymer is a diblock copolymer, a triblock copolymer, or a combination thereof.
[0054] In one aspect, the hydrogenated block copolymer contains no monomer residues other than alkenyl aromatic compounds and conjugated dienes. In one aspect, the hydrogenated block copolymer is composed of blocks derived from alkenyl aromatic compounds and conjugated dienes. It does not contain grafts formed from these or any other monomers. It also consists of carbon atoms and hydrogen atoms and is therefore free of heteroatoms. In one aspect, the hydrogenated block copolymer contains residues of one or more acid functionalizing agents (e.g., maleic anhydride). In one aspect, the hydrogenated block copolymer comprises a polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer.
[0055] In one aspect, the hydrogenated block copolymer is a polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer and has a polystyrene content of 10 to 50 weight percent, or 20 to 40 weight percent, or 20 to 35 weight percent, or 25 to 35 weight percent, based on the weight of the polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer. In these aspects, the polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer optionally has a weight average molecular weight of 200,000 to 400,000 g / mol, or 250,000 to 350,000 g / mol, as determined by size exclusion chromatography using polystyrene standards.
[0056] Methods for preparing hydrogenated block copolymers are well known in the art, and many hydrogenated block copolymers are commercially available. Examples of commercially available hydrogenated block copolymers include: TM Polystyrene-poly(ethylene-propylene) diblock copolymers of G1701 (with 37 wt. % polystyrene) and G1702 (with 28 wt. % polystyrene); supplied by Kraton Performance Polymers Inc. under the name KRATON TM polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymers of G1641 (33 wt% polystyrene), G1650 (30 wt% polystyrene), G1651 (33 wt% polystyrene), and G1654 (31 wt% polystyrene); and Kuraray's SEPTON TM Polystyrene-poly(ethylene-ethylene / propylene)-polystyrene triblock copolymers of S4044, S4055, S4077, and S4099. Other commercially available hydrogenated block copolymers include those offered by Dynasol under the name CALPRENE TM Polystyrene-poly(ethylene-butylene)-polystyrene (SEBS) triblock copolymers of H6140 (31 wt% polystyrene), H6170 (33 wt% polystyrene), H6171 (33 wt% polystyrene), and H6174 (33 wt% polystyrene); and SEPTON supplied by Kuraray TM 8006 (33 wt% polystyrene) and 8007 (30 wt% polystyrene) polystyrene-poly(ethylene-butylene)-polystyrene (SEBS) triblock copolymers; supplied by Kuraray under the name SEPTON TM Polystyrene-poly(ethylene-propylene)-polystyrene (SEPS) copolymers of 2006 (35 wt% polystyrene) and 2007 (30 wt% polystyrene); and oil-extended compounds of these hydrogenated block copolymers, available from Kraton Performance Polymers as KRATON TM G4609 (containing 45% mineral oil and SEBS with 33% polystyrene by weight) and G4610 (containing 31% mineral oil and SEBS with 33% polystyrene); TUFTEC available from Asahi TMH1272 (SEBS containing 36% oil and 35% by weight polystyrene). Mixtures of two or more hydrogenated block copolymers can also be used. In one aspect, the hydrogenated block copolymer comprises a polystyrene poly(ethylene-butylene)-polystyrene triblock copolymer having a weight average molecular weight of at least 100,000 g / mol, or from 200,000 to 400,000 g / mol.
[0057] The composition comprises 1 to 15 weight percent of the hydrogenated block copolymer, based on the total weight of the composition. Within this range, the hydrogenated block copolymer can be present in an amount of 1 to 10 weight percent, 2 to 10 weight percent, 3 to 10 weight percent, 3 to 8 weight percent, 5 to 10 weight percent, 4 to 8 weight percent, or 5 to 7 weight percent.
[0058] In one aspect, other impact modifiers besides the hydrogenated block copolymer can be minimized (ie, present at less than 1 weight percent) or excluded from the thermoplastic composition. For example, homopolystyrene or high impact polystyrene can be eliminated from the composition.
[0059] The thermoplastic composition may optionally further include an additive composition. The additive composition includes one or more additives. These additives can be, for example, stabilizers, release agents, lubricants, processing aids, drip-proof agents (dripretardant), nucleating agents, UV blockers, dyes, pigments, antioxidants, antistatic agents, blowing agents (blowing agents), mineral oils, metal passivators, antiblocking agents (antiblocking agents), or combinations thereof. In one aspect, the additive composition can include antioxidants, lubricants, heat stabilizers, UV absorbing additives, plasticizers, drip-proof agents (anti-dripping agent), release agents, antistatic agents, dyes, pigments, laser marking additives, radiation stabilizers, or combinations thereof. When adding such additives, their total amount is typically 0.1 to 10 weight % of the total weight of the composition.
[0060] In one aspect, the composition may include an anti-drip agent. Fluorinated polyolefins or polytetrafluoroethylene can be used as anti-drip agents. Anti-drip agents can also use, for example, fluoropolymers that form fibrils or do not form fibrils, such as polytetrafluoroethylene (PTFE). Anti-drip agents can be coated with a rigid copolymer, such as styrene-acrylonitrile (SAN). PTFE coated in SAN is known as TSAN. Coated fluoropolymers can be prepared by polymerizing the coating polymer in the presence of a fluoropolymer, such as in an aqueous dispersion. TSAN can provide significant advantages over PTFE because it is more easily dispersed in the composition. A suitable TSAN can contain, for example, 50 wt% (weight %) PTFE and 50 wt% SAN (based on the total weight of the coated fluoropolymer). For example, SAN can contain 75 wt% styrene and 25 wt% acrylonitrile, based on the total weight of the copolymer. Alternatively, the fluoropolymer can be premixed with a second polymer, such as an aromatic polycarbonate resin or SAN, to form an agglomerated material for use as an anti-drip agent. Both methods can be used to produce encapsulated fluoropolymers.
[0061] The anti-drip agent can be added in the form of larger particles with a number average particle size of 0.3 to 0.7 mm, especially 0.4 to 0.6 mm. The amount of the anti-drip agent used is 0.01 wt% to 5.0 wt% of the total weight of the composition.
[0062] The thermoplastic composition comprises less than 1% by weight of a hydrocarbon resin, based on its total weight. Preferably, the composition may be free of hydrocarbon resin. As used herein, the term "hydrocarbon resin" refers to aliphatic hydrocarbon resins, hydrogenated aliphatic hydrocarbon resins, aliphatic / aromatic hydrocarbon resins, hydrogenated aliphatic / aromatic hydrocarbon resins, cycloaliphatic hydrocarbon resins, hydrogenated cycloaliphatic resins, cycloaliphatic / aromatic hydrocarbon resins, hydrogenated cycloaliphatic / aromatic hydrocarbon resins, hydrogenated aromatic hydrocarbon resins, terpene resins, hydrogenated terpene resins, terpene-phenol resins, rosin and rosin esters, hydrogenated rosin and rosin esters, and mixtures thereof. As used herein, "hydrogenated" refers to hydrocarbon resins and includes fully hydrogenated, substantially hydrogenated, and partially hydrogenated resins. Aromatic resins may include aromatic-modified aliphatic resins, aromatic-modified alicyclic resins, and hydrogenated aromatic hydrocarbon resins, wherein the aromatic content may be 1 to 30% by weight. Any of the above resins may be grafted with an unsaturated ester or anhydride. In one aspect, the composition can be free of hydrogenated aromatic hydrocarbon resins.
[0063] The composition may optionally minimize or exclude additional components not specifically described herein. For example, the composition comprises less than 5 wt %, or less than 2 wt %, or less than 1 wt %, or less than 0.1 wt % of a flame retardant synergist (e.g., phosphazene). In one aspect, the composition does not comprise a flame retardant synergist, such as phosphazene. In one aspect, the composition may not comprise any thermoplastic polymer other than the above-mentioned polymer of the present composition. In one aspect, the composition may minimize or exclude homopolystyrene or rubber-modified polystyrene. In one aspect, the composition may minimize or exclude tricalcium phosphate.
[0064] In a specific aspect, the thermoplastic composition can include: 20 to 38 weight percent of a first poly(phenylene ether); 20 to 38 weight percent of a poly(phenylene ether)-poly(siloxane) block copolymer reaction product, the reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); 8 to 32 weight percent of a reinforcing filler; 12 to 20 weight percent of an organophosphate flame retardant; and 2 to 10 weight percent of an impact modifier comprising a hydrogenated block copolymer of an alkenyl arene and a conjugated diene; wherein the weight percent of each component is based on the total weight of the composition; and wherein the weight ratio of the first poly(phenylene ether) to the poly(phenylene ether)-poly(siloxane) block copolymer reaction product is from 1.75:1 to 1:1.75. The first poly(phenylene ether) may include poly(2,6-dimethyl-1,4-phenylene oxide) and have an intrinsic viscosity of 0.25 to 0.6 dL / g as measured in chloroform at 25°C using an Ubbelohde viscometer. The reinforcing filler may include glass fiber. The hydrogenated block copolymer may include polystyrene-poly(ethylene-butylene)-polystyrene. The organophosphate flame retardant may include bisphenol A bisdiphenyl phosphate.
[0065] The compositions herein can exhibit an ideal combination of properties. For example, molded samples of the composition can achieve a UL-94 flammability rating of V0 when measured using a 1.0 mm test bar after acclimation at 23°C for 48 hours and 70°C for 168 hours; a UL-94 flammability rating of V0 when measured using a 0.75 mm test bar after acclimation at 23°C for 48 hours and 70°C for 168 hours; a UL-94 flammability rating of V0 when measured using a 0.5 mm test bar after acclimation at 23°C for 48 hours and 70°C for 168 hours; and a UL-94 flammability rating of V0 when measured using a 0.3 mm test bar after acclimation at 23°C for 48 hours and 70°C for 168 hours. Molded samples of the composition can also exhibit desirable mechanical properties, such as a tensile modulus of 3500 MPa or greater as measured in accordance with ASTM D638.
[0066] The composition herein can be prepared, for example, by melt blending the components of the composition. The components of the composition can be blended using conventional equipment (e.g., ribbon blenders, HENSCHEL TM Mixer, Banbury TM The mixture is mixed or blended in a mixer (e.g., a drum mixer, etc.), and the blended composition can then be melt-blended or melt-kneaded. Melt blending or melt-kneading can be performed using conventional equipment (e.g., a single-screw extruder, a twin-screw extruder, a multi-screw extruder, a blending kneader, etc.). For example, the present composition can be prepared by melt-blending the components in a twin-screw extruder at a temperature of 270-310° C. or 280-300° C. The extrudate can be immediately quenched in a water bath and pelletized. The pellets thus prepared can be a quarter inch long or shorter as desired. Such pellets can be used for subsequent molding, shaping, or forming.
[0067] Shaped, formed or molded articles comprising the composition represent another aspect of the present invention. The composition can be molded into useful shaped articles by a variety of methods, such as injection molding, extrusion, rotational molding, blow molding, and thermoforming. Some examples of articles include electric vehicle battery modules, battery housings, battery cases, battery cell frames, battery cell spacers, battery cell holders, battery pack insulation films, bus bar holders, terminal covers, electrical or electronic components, thermoset circuit breakers, fuse holders for electrostatic copiers, photovoltaic junction boxes, photovoltaic connectors, electrical connectors, automotive electrical connectors, relays, charge couplers, appliance parts, automotive parts, portable devices, mobile parts, or fixed electrical parts. In one aspect, the article is an extruded article, a molded article, a pultruded article, a thermoformed article, a foamed article, a layer of a multilayer article, a substrate for a coated article, or a substrate for a metallized article. In one aspect, the composition is particularly suitable for use in molded or extruded components of electric vehicle battery components. For example, the composition can be used in extruded components of electric vehicle battery components, such as insulating sheets or films of electric vehicle battery components.
[0068] An electric vehicle battery assembly extruded from the composition of the present disclosure represents another aspect of the present disclosure. The electric vehicle battery component can be an electric vehicle battery insulating sheet or film. The electric vehicle battery insulating sheet or film can be prepared by extruding the composition herein to provide the desired sheet or film. In one aspect, the extruded film or sheet can have a UL-94 flammability rating of V0 measured using a 1.0 mm test rod after acclimation at 23°C for 48 hours and acclimation at 70°C for 168 hours; a UL-94 flammability rating of V0 measured using a 0.75 mm test rod after acclimation at 23°C for 48 hours and acclimation at 70°C for 168 hours; a UL-94 flammability rating of V0 measured using a 0.5 mm test rod after acclimation at 23°C for 48 hours and acclimation at 70°C for 168 hours; and a UL-94 flammability rating of V0 measured using a 0.3 mm test rod after acclimation at 23°C for 48 hours and acclimation at 70°C for 168 hours. The extruded film or sheet may optionally further exhibit one or both of the following: a heat distortion temperature greater than or equal to 115° C. as measured on a 3.2 mm thick test bar at a load of 1.82 MPa according to ASTM D648; and a relative tracking resistance PLCO as measured according to ASTM D3638. The battery insulating film may have a thickness of, for example, 50 to 1000 μm.
[0069] As described herein, the inventors have unexpectedly discovered that compositions comprising specific amounts of the components described herein can provide certain advantageous properties. Specifically, a combination of high mechanical strength, high heat resistance, high impact strength, and low flammability can be achieved, particularly for thin-walled molded articles. Consequently, significant improvements are provided herein, particularly with respect to battery pack insulating films or sheets extruded from such compositions.
[0070] The present invention is further illustrated by the following non-limiting examples. Example
[0071] The materials used in the following examples are shown in Table 1.
[0072] Table 1
[0073]
[0074] Each composition was compounded using a Toshiba TEM-37BS twin-screw extruder. All components were added through the extruder inlet, except for BPADP, which was added via a liquid feeder in zone 3, and glass fiber, which was added via a side feeder in zone 7. The extrudate was cooled in a water bath and pelletized. The pellets were conditioned at 120°C for 3 hours before injection molding or extrusion. The process parameters are summarized in Table 2.
[0075] Table 2
[0076] Screw design L-2-1 Feed (zone 0) temperature -- Zone 1 temperature 50℃ Zone 2 temperature 150℃ Zone 3 temperature 240℃ Zone 4 temperature 280℃ Zone 5 temperature 280℃ 6-zone temperature 280℃ 7-zone temperature 300℃ 8-zone temperature 300℃ 9 zone temperature 300℃ 10 zone temperature 280℃ Zone 11 Temperature 280℃ 12 zone temperature -- Die temperature 290℃ Screw speed 300rpm Throughput 30kg / hr Torque 45% Side feeder 1 speed 250rpm
[0077] The test pieces were injection molded on a Toshiba UH1000-110 injection molding machine with barrel temperatures of 290°C, 300°C, 300°C, and 290°C (from feed throat to nozzle) and a mold temperature of 90°C during operation.
[0078] Various properties of the molded parts were tested according to the following standards.
[0079] Melt flow rate values are in g / 10 min and are measured according to ASTM D1238-10 Method B at 300°C and a 5 kg load.
[0080] Heat deflection temperature (HDT) is measured in °C at 1.82 MPa or 0.45 MPa using a 3.2 mm thick bar according to ASTM D648.
[0081] Notched Izod impact strength (NII) values are reported in Joules per meter and are measured according to ASTM D 256-10, Method A, at 23°C using a bar having a cross-sectional dimension of 3.2 mm x 12.7 mm. Unnotched Izod impact strength (UNII) is reported in Joules per meter and is measured according to ASTM D 4812 at 23°C using a bar having a cross-sectional dimension of 3.2 mm x 12.7 mm.
[0082] The tensile properties were measured according to ASTM D638, with a sample thickness of 3.2 mm and a test speed of 5 mm / min.
[0083] The flame retardancy of injection-molded flame bars was determined according to the Underwriter's Laboratory Bulletin 94, "Tests for Flammability of Plastic Materials, UL 94," 20 mm Vertical Burning Flame Test. According to this procedure, materials are classified as HB, V0, UL94 V1, V2, 5VA, and / or 5VB based on the test results from five samples, or for 5VB, based on the test results from three samples. Prior to testing, flame bars with thicknesses of 1.0, 0.75, 0.5, 0.3, and 0.2 mm were conditioned at 23°C and 50% relative humidity for at least 48 hours, or at 70°C and 50% relative humidity for 168 hours. A group of 10 to 20 flame bars was tested in the UL 94 20 mm Vertical Burning Flame Test. For each fire barrier strip, a flame is applied for 10 seconds, then removed, and the time it takes for the strip to self-extinguish (first after flame time, t1) is recorded. The flame is then reapplied for 10 seconds and removed, and the time it takes for the strip to self-extinguish (second after flame time, t2) and the post-flame glowing time (afterglow time, t3) are recorded. To achieve a V-0 rating, the flaming time t1 and t2 of each sample must be less than or equal to 10 seconds; the total flaming time of all five samples (t1 plus t2 for all five samples) must be less than or equal to 50 seconds; the second after flame time plus the afterglow time (t2 + t3) of each sample must be less than or equal to 30 seconds; none of the samples burn with or without flame to the retaining clip; and the cotton indicator cannot be ignited by burning particles or drippings. To achieve the V-1 rating, the flaming burning time t1 and t2 of each sample must be less than or equal to 30 seconds; and the total flaming burning time of all five samples (t1 plus t2 of all five samples) must be less than or equal to 250 seconds; and the second flaming burning time plus the flameless burning time (t2 + t3) of each sample must be less than or equal to 60 seconds; and none of the samples burns flamingly or flamelessly to the retaining clip; and the cotton indicator cannot be ignited by burning particles or dripping objects.To achieve a V-2 rating, the flaming burn time t1 and t2 of each sample must be less than or equal to 30 seconds; and the total flaming burn time of all five samples (t1 plus t2 of all five samples) must be less than or equal to 250 seconds; and the second flaming burn time plus the flameless burn time (t2 + t3) of each sample must be less than or equal to 60 seconds; and no sample will burn flamingly or flamelessly to the retaining clip; but the cotton indicator can be ignited by burning particles or drippings.
[0084] To obtain a 5VB rating, a flame is applied to a vertically mounted 5-inch (127mm) x 0.5-inch (12.7mm) test bar of given thickness, with a dry, absorbent cotton pad placed 12 inches (305mm) below it. The thickness of the test bar is measured with a caliper with an accuracy of 0.1mm. The flame is 5 inches (127mm) in diameter and the inner blue cone is 1.58 inches (40mm) in diameter. The flame is applied to the test bar for 5 seconds, so that the tip of the blue cone touches the lower corner of the sample. The flame is then removed for 5 seconds. The application and removal of the flame is repeated until the sample has been applied with the same flame five times. After the fifth application of the flame, the flame is removed and a timer (T-0) is started to measure the time the sample continues to burn (flaming time) and the time the sample continues to glow after the flaming combustion is extinguished (flameless time). The method is to stop T-0 when the flaming combustion stops, unless flameless combustion occurs, in which case T-0 is stopped when the flameless combustion stops. After applying the flame five times to the test bar, the sum of the flaming and flameless burning times must be less than or equal to 60 seconds, and no dripping should ignite the cotton pad. This test is repeated on five identical test bar samples. If one of the five samples does not meet the time and / or no dripping requirements, a second set of five samples is tested in the same manner. All of the samples in the second set of five samples must meet all requirements for the material of a given thickness to meet the 5VB standard.
[0085] To achieve a 5VA rating, testing is performed on both test bars and plaque specimens. Test bar test procedure: The test bar is held vertically, and a flame is applied at a 20° angle to one of the lower corners of the specimen. The flame is applied for 5 seconds and then removed for 5 seconds. The application and removal of the flame is repeated five times. Test plaque test procedure: The test plaque differs from the test bar test in that the specimen is held horizontally, and the flame is applied to the center of the lower surface of the specimen. To achieve a 5VA rating, the specimen must not exhibit any flaming or flameless combustion within 60 seconds after five applications of the flame. The specimen must not drip flaming particles that could ignite the cotton. The test plaque must not exhibit burn-throughs (holes).
[0086] Hydrolytic stability is assessed by placing tensile test bars in a hydrolysis chamber at 85°C and 85% relative humidity for 1000 hours. The samples are then removed from the chamber and evaluated. Hydrolytic stability is assessed by retention of tensile modulus and tensile stress. Tensile modulus and tensile stress retention of 90% or greater are considered "good." If at least one of the tensile modulus or tensile stress retention is less than 90%, hydrolytic stability is considered "poor."
[0087] The compositions and their various properties are summarized in Table 3. The amount of each component is expressed as wt % based on the total weight of the composition.
[0088] Table 3
[0089]
[0090]
[0091] Table 3 (continued)
[0092]
[0093]
[0094] As shown in Table 3, each composition exhibited good dimensional stability and hydrolysis resistance. However, Comparative Example 1 (CE1), which contains only PPE as a matrix and 10% glass fiber, only achieved a V1 rating at 1 mm and 0.75 mm, and a V2 rating at 0.5 mm and 0.3 mm. When the glass fiber content was increased to 30% in Comparative Example 2 (CE2), a V2 rating was achieved across all thicknesses from 0.3 to 1 mm. Comparative Example 3 (CE3), which contains 20% glass fiber and a PPE-Si matrix, exhibited a V1 rating at all tested thicknesses. Therefore, none of the comparative compositions achieved a V0 rating at a thickness of 1 mm or less. Furthermore, none of the comparative compositions achieved a "pass" rating of UL94 5VA or 5VB at a thickness of 1.5 mm.
[0095] In contrast, the compositions of Examples 1-4 demonstrate that the combination of PPE, PPE-Si, and glass fiber can achieve the desired flame retardancy properties, particularly for thin-wall applications, while maintaining other mechanical properties. Specifically, Example 1, comprising PPE, PPE-Si, and 10% glass fiber, exhibited a V0 rating across all tested thicknesses from 0.3 to 1 mm. It also achieved a UL94 5VA "Pass" rating at 1.5 mm. Increasing the glass fiber content to 20% in Example 2 exhibited similar flame retardancy, and an increase in tensile modulus was also observed relative to the composition of Example 1. Further increasing the glass fiber content to 30% in Example 3 exhibited similar flame retardancy, and a further increase in tensile modulus was also observed relative to the compositions of Examples 1 and 2. The composition of Example 4 is similar to that of Example 1, but further includes carbon black, and similar properties were observed.
[0096] Table 3 further shows that in Comparative Examples 4 and 5, reducing the BPADP loading to below 10 wt % did not achieve the desired flame performance at thicknesses of 1.0 mm or less.
[0097] Examples 6-12 in Table 3 further demonstrate that the desired combination of properties can be achieved using other fillers, such as carbon fibers. The compositions of Examples 6-12 also demonstrate that an impact modifier may not be necessary.
[0098] Therefore, the combination of PPE and PPE-Si can achieve ideal thin-wall flame retardancy without sacrificing other properties. Therefore, this paper provides a significant improvement. This paper also includes the following aspects.
[0099] Aspect 1: A thermoplastic composition comprising: 20 to 40 weight percent of a first poly(phenylene ether); 20 to 40 weight percent of a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); 8 to 35 weight percent of a reinforcing filler; 10 to 20 weight percent of an organophosphate flame retardant; and optionally, 1 to 15 weight percent of an impact modifier comprising a hydrogenated block copolymer of an alkenyl aromatic hydrocarbon and a conjugated diene; wherein the weight percents of each component are based on the total weight of the composition; and the thermoplastic composition comprises less than 1 weight percent of a hydrocarbon resin, preferably the thermoplastic composition does not contain a hydrocarbon resin.
[0100] Aspect 2: The thermoplastic composition of Aspect 1, wherein the weight ratio of the first poly(phenylene ether) to the poly(phenylene ether)-poly(siloxane) block copolymer reaction product is 1.75:1 to 1:1.75, or 1.5:1 to 1:1.5, or 1.25:1 to 1:1.25, or 1.1:1 to 1:1.1, or 1.05:1 to 1:1.05.
[0101] Aspect 3: The thermoplastic composition of Aspect 1 or 2, wherein the first poly(phenylene ether) has an intrinsic viscosity greater than or equal to 0.25 deciliter / gram, or 0.25 to 0.6 deciliter / gram, or 0.25 to 0.4 deciliter / gram, as measured using an Ubbelohde viscometer in chloroform at 25°C; preferably, wherein the first poly(phenylene ether) comprises poly(2,6-dimethyl-1,4-phenylene ether).
[0102] Aspect 4: The thermoplastic composition according to any one of aspects 1 to 3, wherein the reinforcing filler is reinforcing fiber, preferably the reinforcing fiber comprises glass fiber, carbon fiber, mineral fiber or a combination thereof.
[0103] Aspect 5: The thermoplastic composition according to any one of aspects 1 to 4, wherein the reinforcing filler comprises glass fiber or carbon fiber.
[0104] Aspect 6: The thermoplastic composition according to any one of aspects 1 to 5, wherein the impact modifier is present and comprises a hydrogenated block copolymer comprising polystyrene-poly(ethylene-butylene)-polystyrene.
[0105] Aspect 7: The thermoplastic composition according to any one of aspects 1 to 6, wherein the organic phosphate flame retardant comprises resorcinol bisdiphenyl phosphate, bisphenol A bisdiphenyl phosphate, resorcinol bis(di-2,6-dimethylphenyl) phosphate, oligomeric phosphate, triphenyl phosphate or a combination thereof, preferably bisphenol A bisdiphenyl phosphate.
[0106] Aspect 8: The thermoplastic composition according to any one of aspects 1 to 7, further comprising 0.1 to 10 wt% of an additive composition.
[0107] Aspect 9: The thermoplastic composition of aspect 1, comprising: 20 to 38 weight percent of a first poly(phenylene ether); 20 to 38 weight percent of a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); 8 to 32 weight percent of a reinforcing filler; 12 to 20 weight percent of an organophosphate flame retardant; and 2 to 10 weight percent of an impact modifier comprising a hydrogenated block copolymer of an alkenyl aromatic hydrocarbon and a conjugated diene; wherein the weight percent of each component is based on the total weight of the composition; and the weight ratio of the first poly(phenylene ether) and the poly(phenylene ether)-poly(siloxane) block copolymer reaction product is 1.75:1 to 1:1.75.
[0108] Aspect 10: The thermoplastic composition of Aspect 9, wherein the first poly(phenylene ether) comprises poly(2,6-dimethyl-1,4-phenylene oxide) and has an intrinsic viscosity of 0.25 to 0.6 deciliter / gram, measured using an Ubbelohde viscometer in chloroform at 25°C; the reinforcing filler comprises glass fiber or carbon fiber; the hydrogenated block copolymer comprises polystyrene-poly(ethylene-butylene)-polystyrene; and the organophosphate flame retardant comprises bisphenol A bisdiphenyl phosphate.
[0109] Aspect 11: A thermoplastic composition according to any one of aspects 1 to 10, wherein a molded sample of the composition exhibits: a UL-94 flammability rating of V0 measured using a 1.0 mm test bar after aging at 23°C for 48 hours and aging at 70°C for 168 hours; a UL-94 flammability rating of V0 measured using a 0.75 mm test bar after aging at 23°C for 48 hours and aging at 70°C for 168 hours; a UL-94 flammability rating of V0 measured using a 0.5 mm test bar after aging at 23°C for 48 hours and aging at 70°C for 168 hours; and a UL-94 flammability rating of V0 measured using a 0.3 mm test bar after aging at 23°C for 48 hours and aging at 70°C for 168 hours.
[0110] Aspect 12: The thermoplastic composition according to any one of aspects 1 to 11, wherein a molded sample of the composition exhibits a tensile modulus of 3500 MPa or greater as measured according to ASTM D638.
[0111] Aspect 13: A method of preparing the composition of any one of Aspects 1 to 12, comprising melt mixing the components of the composition.
[0112] Aspect 14: An article comprising the composition of any one of aspects 1 to 12.
[0113] Aspect 15: The article according to Aspect 14, wherein the article is an electric vehicle battery module, a battery housing, a battery box, a battery cell frame, a battery cell spacer, a battery cell holder, a bus bar bracket, a terminal cover, an electrical or electronic component, a thermoset circuit breaker, a fuse holder for an electrostatic copier, a photovoltaic junction box, a photovoltaic connector, an electrical connector, an automotive electrical connector, an electrical relay, a charging coupler, an appliance component, an automotive component, a portable device, a mobile component or a fixed electrical component.
[0114] Aspect 16: A thermoplastic composition comprising: a first poly(phenylene ether); a poly(phenylene ether)-poly(siloxane) block copolymer reaction product, the reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); a reinforcing filler; an organophosphate flame retardant; and optionally an impact modifier comprising a hydrogenated block copolymer of an alkenyl arene and a conjugated diene; wherein the thermoplastic composition comprises less than 1 wt. % hydrocarbon resin, preferably hydrocarbon resin is not included in the thermoplastic composition; and wherein a molded sample of the composition exhibits: conditioned at 23° C. for 48 hours and conditioned at 70° C. for 48 hours; The UL-94 flammability rating measured using a 1.0 mm test rod after 168 hours is V0; the UL-94 flammability rating measured using a 0.75 mm test rod after treating at 23°C for 48 hours and at 70°C for 168 hours is V0; the UL-94 flammability rating measured using a 0.5 mm test rod after treating at 23°C for 48 hours and at 70°C for 168 hours is V0; the UL-94 flammability rating measured using a 0.3 mm test rod after treating at 23°C for 48 hours and at 70°C for 168 hours is V0; and the tensile modulus measured according to ASTM D638 is 3500 MPa or greater.
[0115] The compositions, methods and articles may alternatively comprise, consist of or consist essentially of any suitable material, step or component disclosed herein. In addition, or as an alternative, the compositions, methods and articles may be formulated to be free of or essentially free of any material (or species), step or component that is not necessary to achieve the function or purpose of the compositions, methods and articles.
[0116] All ranges disclosed herein include endpoints, and these endpoints can be independently combined with each other. "Combination" includes blends, mixtures, alloys, reaction products, etc. "First", "second" and other terms do not indicate any order, quantity or importance, but are used to distinguish one element from another. "A" and "an" and "the" and other terms do not indicate quantitative limitations and should be understood to cover both the singular and the plural, unless otherwise specified herein or the context clearly contradicts. "Or" means "and / or", unless otherwise explicitly stated. "An aspect" mentioned throughout this specification refers to a specific element described in association with that aspect that is included in at least one aspect described herein, and may or may not be present in other aspects. The term "combination thereof" used herein includes one or more listed elements and is open, allowing the presence of one or more unmentioned similar elements. In addition, it should be understood that the elements described can be combined in any suitable manner in various aspects.
[0117] Unless otherwise specified herein, all test standards are the most current standards in effect on the filing date of this application (or, if priority is claimed, on the filing date of the earliest priority application in which such test standard appears).
[0118] Unless otherwise defined, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in this application contradicts or conflicts with a term in an incorporated reference, the term in this application takes precedence over the conflicting term in the incorporated reference.
[0119] Compounds are described using standard nomenclature. For example, any position not substituted by any designated group is understood to have its valence filled by a designated bond or by a hydrogen atom. A dash ("-") that is not between two letters or symbols is used to indicate the point of attachment of a substituent. For example, -CHO is attached through the carbon atom of the carbonyl group.
[0120] As used herein, the term "hydrocarbyl," whether used alone or as a prefix, suffix, or fragment of another term, refers to a residue containing only carbon and hydrogen. The residue may be aliphatic or aromatic, straight-chain, cyclic, bicyclic, branched, saturated, or unsaturated. It may also include a combination of aliphatic, aromatic, straight-chain, cyclic, bicyclic, branched, saturated, and unsaturated hydrocarbyl moieties. However, when a hydrocarbyl residue is described as substituted, it may optionally include heteroatoms in addition to the carbon and hydrogen members of the substituent residue. Thus, when specifically described as substituted, the hydrocarbyl residue may also include one or more carbonyl groups, amino groups, hydroxyl groups, etc., or it may include heteroatoms within the backbone of the hydrocarbyl residue. The term "alkyl" refers to a branched or straight-chain saturated aliphatic hydrocarbyl group, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, sec-pentyl, n-hexyl, and sec-hexyl. "Alkenyl" refers to a linear or branched monovalent hydrocarbon group having at least one carbon-carbon double bond (e.g., vinyl (-HC=CH2)). "Alkoxy" refers to an alkyl group attached through an oxygen atom (i.e., alkyl-O-), such as methoxy, ethoxy, and sec-butoxy. "Alkylene" refers to a linear or branched saturated divalent aliphatic hydrocarbon group (e.g., methylene (-CH2-) or propylene (-(CH2)3-)). "Cycloalkylene" refers to a divalent cyclic alkylene group, -C n H 2n-x,Where x represents the number of hydrogen atoms substituted by the cyclization. "Cycloalkenyl" refers to a monovalent group having one or more rings and one or more carbon-carbon double bonds in the rings, wherein all ring members are carbon (e.g., cyclopentyl and cyclohexyl). "Aryl" refers to an aromatic hydrocarbon group containing a specified number of carbon atoms, such as phenyl, tropone, indanyl, or naphthyl. "Arylene" refers to a divalent aromatic group. "Alkylarylene" refers to an arylene substituted with an alkyl group. "Arylalkylene" refers to an alkylene substituted with an aryl group (e.g., benzyl). The prefix "halogen" refers to a group or compound containing one or more of fluorine, chlorine, bromine, or iodine substituents. There can be a combination of different halogen atoms (e.g., bromine and fluorine), or only chlorine atoms. The prefix "hetero" indicates that at least one ring member of the compound or group is a heteroatom (e.g., 1, 2, or 3 heteroatoms), wherein the heteroatoms are each independently N, O, S, Si, or P. "Substituted" means that the compound or group is replaced by at least one (e.g., 1, 2, 3, or 4) substituents in place of hydrogen, each independently C, C, or D, provided that the normal valence of the replaced atom is not exceeded. 1-9 Alkoxy, C 1-9 Haloalkoxy, nitro (-NO2), cyano (-CN), C 1-6 Alkylsulfonyl (-S(=O)2-alkyl), C 6-12 Arylsulfonyl (-S(=O)2-aryl), mercapto (-SH), thiocyano (-SCN), toluenesulfonyl (CH3C6H4SO2-), C 3-12 Cycloalkyl, C 2-12 Alkenyl, C 5-12 Cycloalkenyl, C 6-12 Aryl, C 7-13 Aralkyl, C 4-12 Heterocycloalkyl, and C 3-12 Heteroaryl. The number of carbon atoms shown in the group does not include any substituents. For example, -CH2CH2CN represents a C2 alkyl group substituted with a nitrile.
[0121] While specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are presently unforeseen or may not be foreseen may occur to the applicant or those skilled in the art. Accordingly, the appended claims (as filed and as they may be amended) are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.
Claims
1. A thermoplastic composition comprising: 20-40 wt% of a first poly(phenylene ether); 20 to 40 weight percent of a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); 8 to 35 weight percent of a reinforcing filler; 10-20 wt% of an organophosphate flame retardant; and Optionally, 1 to 15 weight percent of an impact modifier comprising a hydrogenated block copolymer of an alkenyl aromatic hydrocarbon and a conjugated diene; wherein the weight % of each component is based on the total weight of the composition; and The thermoplastic composition comprises less than 1 wt% of a hydrocarbon resin, and preferably the thermoplastic composition does not contain a hydrocarbon resin.
2. The thermoplastic composition of claim 1 , wherein the first poly(phenylene ether) and the poly(phenylene ether)-poly(siloxane) block copolymer reaction product are present in a weight ratio of 1.75:1 to 1:1.75, or 1.5:1 to 1:1.5, or 1.25:1 to 1:1.25, or 1.1:1 to 1:1.1, or 1.05:1 to 1:1.
05.
3. The thermoplastic composition of claim 1 or 2, wherein the first poly(phenylene ether) has an intrinsic viscosity greater than or equal to 0.25 deciliter / gram, or from 0.25 to 0.6 deciliter / gram, or from 0.25 to 0.4 deciliter / gram, as measured in chloroform at 25°C using an Ubbelohde viscometer; Preferably, the first poly(phenylene ether) comprises poly(2,6-dimethyl-1,4-phenylene ether).
4. The thermoplastic composition according to any one of claims 1 to 3, wherein the reinforcing filler is reinforcing fiber, preferably the reinforcing fiber comprises glass fiber, carbon fiber, mineral fiber or a combination thereof.
5. The thermoplastic composition of any one of claims 1 to 4, wherein the reinforcing filler comprises glass fibers or carbon fibers.
6. The thermoplastic composition of any one of claims 1 to 5, wherein the impact modifier is present and comprises a hydrogenated block copolymer comprising polystyrene-poly(ethylene-butylene)-polystyrene.
7. The thermoplastic composition of any one of claims 1 to 6, wherein the organic phosphate flame retardant comprises resorcinol bisdiphenyl phosphate, bisphenol A bisdiphenyl phosphate, resorcinol bis(di-2,6-dimethylphenyl) phosphate, oligomeric phosphate, triphenyl phosphate or a combination thereof, preferably bisphenol A bisdiphenyl phosphate.
8. The thermoplastic composition of any one of claims 1 to 7, further comprising 0.1 to 10 weight percent of an additive composition.
9. The thermoplastic composition of claim 1 , comprising: 20 to 38 weight percent of a first poly(phenylene ether); 20 to 38 weight percent of a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); 8 to 32 weight percent of a reinforcing filler; 12 to 20 weight percent of an organic phosphate flame retardant; and 2 to 10 weight percent of an impact modifier comprising a hydrogenated block copolymer of an alkenyl aromatic hydrocarbon and a conjugated diene; wherein the weight % of each component is based on the total weight of the composition; and The weight ratio of the first poly(phenylene ether) to the reaction product of the poly(phenylene ether)-poly(siloxane) block copolymer is 1.75:1 to 1:1.
75.
10. The thermoplastic composition of claim 9, wherein The first poly(phenylene ether) comprises poly(2,6-dimethyl-1,4-phenylene ether) and has an intrinsic viscosity of 0.25 to 0.6 deciliter / gram as measured in chloroform at 25° C. using an Ubbelohde viscometer; Reinforcing fillers include glass fibers or carbon fibers; The hydrogenated block copolymer comprises polystyrene-poly(ethylene-butylene)-polystyrene; and Organic phosphate flame retardants include bisphenol A bisdiphenyl phosphate.
11. The thermoplastic composition of any one of claims 1 to 10, wherein a molded sample of the composition exhibits: The UL-94 flammability rating is V0, measured using a 1.0 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours; The UL-94 flammability rating is V0, measured using a 0.75 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours; UL-94 flammability rating of V0, measured using a 0.5 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours; and The UL-94 flammability rating is V0, measured using a 0.3 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours.
12. The thermoplastic composition according to any one of claims 1 to 11, wherein A molded sample of the composition exhibits a tensile modulus of 3500 MPa or greater, as measured according to ASTM D638.
13. A process for preparing a composition according to any one of claims 1 to 12, which process comprises melt mixing the components of the composition.
14. An article comprising the composition of any one of claims 1 to 12, optionally wherein the article is an electric vehicle battery module, a battery housing, a battery case, a battery cell frame, a battery cell spacer, a battery cell holder, a busbar support, a terminal cover, an electrical or electronic component, a thermoset circuit breaker, a fuse holder for an electrostatic copier, a photovoltaic junction box, a photovoltaic connector, an electrical connector, an automotive electrical connector, an electrical relay, a charging coupler, an appliance component, an automotive component, a portable device, a mobile component, or a fixed electrical component.
15. A thermoplastic composition comprising: a first poly(phenylene ether); a poly(phenylene ether)-poly(siloxane) block copolymer reaction product comprising a poly(phenylene ether)-poly(siloxane) block copolymer and a second poly(phenylene ether); reinforcing fillers; Organophosphate flame retardants; and Optionally, an impact modifier comprising a hydrogenated block copolymer of an alkenyl arene and a conjugated diene; wherein the thermoplastic composition comprises less than 1 wt. % of a hydrocarbon resin, preferably the thermoplastic composition does not contain a hydrocarbon resin; and Among them, molded samples of the composition exhibited: The UL-94 flammability rating is V0, measured using a 1.0 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours; The UL-94 flammability rating is V0, measured using a 0.75 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours; The UL-94 flammability rating is V0, measured using a 0.5 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours; UL-94 flammability rating of V0, measured using a 0.3 mm test rod after acclimation at 23°C for 48 hours and at 70°C for 168 hours; and The tensile modulus is 3500 MPa or greater as measured according to ASTM D638.
Citation Information
Patent Citations
Poly(arylene ether)-polysiloxane composition and method
US8017697B2
Poly(arylene ether)-polysiloxane composition and method
US8669332B2